Using Picture Technique To Improve Students' Speaking Skill At The Sixth Year of SD Muhammadiyah 24 Surakarta: Classroom Action Research - Agus Silo Dwi, Prasetyo (2012)
This study is about the application of picture technique for improving student's speaking mastery at the sixth year of SD Muhammadiyah 24 Surakarta. In this research, the writer uses classroom action research. In this research, the object of the study is the teacher and the student's activity in learning English at the sixth grade in SD Muhammadiyah 24 Surakarta based on the picture technique. The writer conducts the action research of teaching and learning English by using picture technique at the sixth grade of SD Muhammadiyah 24 Surakarta. After observing the implementation of the English teaching-learning process in SD Muhammadiyah 24 Surakarta by using the picture technique, the writer can draw three strength that conclude of learning-concept, such as; structurally concept of learning, the teacher explains clearly, and the learning process is related to daily life. The English teaching learning process at the school consists of four activities, such as: a) Reading aloud, b) Vocabulary, c) Discussion, and d) Question and Answer. From the activities above, so there are any interaction and communication between the teacher and the student. Hence, it is necessary that teachers always rehearse how to manage the student selves prior to teaching in the class especially in teaching of vocabulary by using the picture technique.